Ombrophytum guayanensis, the first record of subfamily Lophophytoideae (Balanophoraceae) in the Guayana Shield - Delprete, Piero G. (Phytotaxa, 2014)
The family Balanophoraceae continues to be poorly known and rarely collected, mostly due to its partially or completely subterranean habit and its general aspect resembling a fungus. A recent collection from French Guiana was identified as a species of Ombrophytum unknown to science (O. guayanensis), which is here described and illustrated. This species also represents the first record of the subfamily Lophophytoideae for the Guayana Shield.